Neonatal scrotochesis following artificial rupture of membrane in breech delivery - Abdelrahman S. Elnour; Alaa Algurashe; Selma Karsani; Amal Alfatih; Moataz Idriss; Omer Ibrahim (Urology Case Reports)
Birth trauma refers to structural or functional impairments in newborns caused by mechanical forces during labour and delivery, with breech presentation significantly increasing the risk of neonatal injuries. Scrotochesis, a disruption of the scrotal wall, is a rare complication associated with vaginal breech birth. We report a neonate who presented with scrotochesis following artificial rupture of membranes (ARM) during a term breech delivery. This case highlights the potential risks associated with breech deliveries and obstetric interventions, emphasizing the importance of careful monitoring and gentle manoeuvres to prevent perineal and scrotal trauma in neonates.